Current Progress and Future Prospects for the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) Genome Editing Technology in Fruit Tree Breeding. (4th July 2018) - Wang, Xianhang; Tu, Mingxing; Li, Zhi; Wang, Yuejin; Wang, Xiping
Abstract: Difficulties in generating woody perennial fruit trees and a lack of molecular markers have impeded functional analysis of agronomically important genes and genetic engineering for improved fruit cultivars. The clustered regularly interspaced short palindromic repeats (CRISPR) technology has been applied in editing fruit tree genomes, providing timely opportunities for studying the functions of the genes in fruit development and stress tolerance. It also leads to the new era of genetic engineering of fruit trees. In this review, we intend to present recent progress in the application of CRISPR to genome editing of fruit trees. We reviewed the most widely used CRISPR systems developed in other plant species that may be adopted for fruit trees and describe three genetic transformation methods used for fruit trees that have potential application value for different CRISPR systems. We also discuss the potential of the CRISPR system to study basic fruit tree biology and for precision fruit tree breeding.